Geographical space and cinema images of the white Arctic on a white screen (Part I) - I. S. Zonn; И. С. Зонн (The Centre of Regional Research, 2023)
The infinity of spaces, open spaces, the “White Silence” of the classical Arctic with a harsh climate, with its ice-bound Arctic Ocean, polar seas, archipelagos, islands covered with glaciers and snow, rocks breaking off into the sea, permafrost has always been a hostile environment, causing human fear. The icy Arctic desert on the shores turns into hard-to-reach areas of tundra, forest tundra and northern taiga. These are Siberia, Alaska, the Canadian Arctic archipelago, the Scandinavian-Icelandic polar regions. But it was their ignorance, their natural riches of furs, fish, forest, gold, and later oil and gas that attracted attention. With the advent of cinema, the Arctic and the North Pole crowning it, actually frozen ocean water, became the object of cinematographers. The whiteness of snow and ice refers us to the white sheet screen. The “white” polar nature appeared on it, affecting the destinies of people living in it, and those who came to master and transform it. The creators of cinema groped their way as well as the conquerors of the North Pole. At the beginning of the twentieth century . world directors Georges Milies, Bester Keaton, Lev Kuleshov, Charlie Chaplin have trodden the fantastic-comedy and dramatic silent cinematic Arctic path with their films. Then there were expedition documentaries, because the operators in the composition of the expeditions had to capture the historical events taking place in truly Arctic conditions, and a little later, feature films sometimes with world movie stars, in which, in accordance with the natural conditions of movement, new performers were introduced — animals, in particular dogs, deer, bears. The image, sound, and movement helped to enhance the demonstration of the color of Arctic landscapes and subjects on a white screen. Gradually, the Arctic occupied its niche in the panorama of world cinema not only as a decoration, but also as a full-fledged socio-geographical “actor”. However, the geography of film production of Arctic films is quite limited, although ...